2016
DOI: 10.5152/tud.2016.84579
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of childhood nephrogenic adenoma in urinary bladder developed four years after previous surgery despite intravesical sodium hyaluronate therapy

Abstract: Nephrogenic adenoma (NA) is a rarely seen benign metaplastic lesion of the urinary tract. Its etiology is uncertain, but induced by chronic inflammation, irritation, and trauma. NA is located in the urinary tract, most commonly in the bladder. NA usually presents with hematuria and lower urinary tract symptoms. In the literature it is mostly seen in adults but about 30 cases of NA's have been reported in children. Treatment of intravesical lesions consists of transurethral resection (TUR) and fulguration and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition to surgical treatment for NA, Campobasso et al [3] successfully treated a 12-year-old boy diagnosed with bladder NA with sodium hyaluronate. Then several reports subsequently confirmed that NA could be successfully treated by injecting sodium hyaluronate into the bladder of children with bladder NA [27] . A recent study also reported the first case of injection of sodium hyaluronate in the bladder to successfully treat adult NA, [4] indicating that sodium hyaluronate could be an alternative treatment for patients who were not suitable for surgical resection of lesions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to surgical treatment for NA, Campobasso et al [3] successfully treated a 12-year-old boy diagnosed with bladder NA with sodium hyaluronate. Then several reports subsequently confirmed that NA could be successfully treated by injecting sodium hyaluronate into the bladder of children with bladder NA [27] . A recent study also reported the first case of injection of sodium hyaluronate in the bladder to successfully treat adult NA, [4] indicating that sodium hyaluronate could be an alternative treatment for patients who were not suitable for surgical resection of lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Then several reports subsequently confirmed that NA could be successfully treated by injecting sodium hyaluronate into the bladder of children with bladder NA. [ 27 ] A recent study also reported the first case of injection of sodium hyaluronate in the bladder to successfully treat adult NA, [ 4 ] indicating that sodium hyaluronate could be an alternative treatment for patients who were not suitable for surgical resection of lesions. Currently, more case reports are needed to provide further evidence that topical application of sodium hyaluronate as an effective treatment option.…”
Section: Discussionmentioning
confidence: 99%